Adrenergic receptor gene expression in bovine leukocytes. (February 2022) - Howell, Angela; Arsic, Natasa; Brownlie, Robert; Griebel, Philip
Abstract: The α- and β-adrenergic receptors (ARs) bind the stress hormones epinephrine (E), norepinephrine (NE), and dopamine and activate diverse physiological responses. A lack of information on AR gene expression in leukocytes limits our understanding of how stress alters immune function. Quantitative analyses of AR gene expression was completed for bovine leukocytes. Individual leukocyte lineages and subpopulations within lineages were isolated with high-speed cell sorting to facilitate a targeted analysis of AR gene expression. These analyses confirmed all 9 AR genes were expressed in bovine leukocytes with marked differences in AR gene expression when comparing among leukocyte lineages. Furthermore, separation of polymorphonuclear cells into neutrophils and eosinophils revealed these key innate immune cells also differ significantly in AR gene expression. This study provides the first comprehensive survey of AR gene expression in immune cells of any mammalian species and provides insight into conflicting reports that stress can either activate or suppress immune function. Graphical abstract: Image 1 Highlights: First comprehensive survey of adrenergic receptor gene expression in leukocytes All 9 adrenergic receptor genes expressed in bovine leukocytes High-speed cell sorting used to purify individual leukocyte lineages Adrenergic receptor gene expression differs among leukocyte lineages Adrenergic receptor gene expression differs between neutrophils and eosinophils